A Fully Integrated 0.48 THz FMCW Radar Sensor in a SiGe Technology - Florian Vogelsang; Jonathan Bott; David Starke; Marc Hamme; Benedikt Sievert; Holger Rucker; Nils Pohl (IEEE Journal of Microwaves)
The THz gap has been a significant research objective for photonics and electronics for decades. This work introduces a fully integrated frequency modulated continuous wave (FMCW) radar sensor with a center frequency of 0.48 THz, realized in a silicon-germanium (SiGe) technology. The sensor consists of a THz MMIC integrated onto a front-end printed circuit board (PCB) with FR4 substrate used for frequency synthesis and IF signal amplification. A dielectric polytetrafluoroethylene (PTFE) lens is mounted above the MMIC to act as transmitter (Tx) and receiver (Rx) lens as well as a physical protection for the bond wires of the MMIC. A back-end PCB generates the supply voltages and control signals, and its analog-digital-converter (ADC) samples the IF signal. The whole sensor is just 4.9 cm by 4.3 cm in size and is cost-efficient due to its design with FR4 PCBs. The MMIC reaches an output power of up to $-9$ dBm. In FMCW operation with the full sensor, a tuning range of 49 GHz is reached along an equivalent isotropic radiated power (EIRP) of up to 22 dBm. Distance measurements were successfully tested for distances of up to 5 m, and a radiation pattern is presented. In summary, this article demonstrates the potential of SiGe technology in the THz range for applications like localization, material characterization, and communication.